Nesting biology and nest survival of the Grassland Sparrow (Ammodramus humeralis) in grazed grasslands of central-eastern Argentina - Colombo, Martín (2021)
Knowledge of the breeding biology of grassland birds is important given the accelerated rate of transformation of their habitats, which has led to noticeable population declines of many species. Although several species in South America are of conservation concern due to habitat alteration, information on their nesting biology is generally sparse. During three seasons we studied a breeding population of a poorly studied ground-nesting bird, the Grassland Sparrow (Ammodramus humeralis), in grasslands used for cattle grazing in central-eastern Argentina. We described its breeding parameters, estimated nestling growth curves, and analyzed daily nest survival rates (DSR) as a function of grassland characteristics, including grass density, grass height, and distance to forest edges. We found 34 nests placed among low and sparse vegetation and made exclusively of grass. The modal clutch size was three eggs. Incubation and nestling periods lasted 11 and 10.5 days, respectively. Nestlings had a fast-growing tarsus, which could be advantageous to escape from predators early. Only seven nests (20.6%) were successful and predation was the principal cause of nest failure (78% of the failures). DSR was 0.91, resulting in a cumulative survival of 11% for the 23.5 day nesting period. We found no effects of habitat features on DSR, which may be a consequence of the high predation rate and a very diverse predator community in the area. Studies at a broader scale could help to elucidate which habitats favor the reproduction of these species. We emphasize the importance of knowing basic ecological aspects of native grassland birds to develop management plans, especially given the lack of protected grassland areas in the Pampas Grassland ecoregion.